Serviço social na educação : um estudo das atribuições profissionais em escolas públicas municipais - Santos, André Michel dos (2019)
This thesis was elaborated based on the theme Social Service in Education and sought to answer the research problem: "What are the duties of the social worker for the work in the area of basic education? "The general objective of the research was to analyze the attributions of the social worker in basic education, in the legislations and public bidding documents referring to the insertion of Social Service in education. As specific objectives, it was intended to identify the attributions of the social worker described in the calls for tenders and in the legislations that deal with the insertion of this professional in the area of education; to investigate the demands, attributions and strategies of the Social Service in the municipal basic education and to deepen the knowledge about the politics of basic education and Social Work in education. The study was guided by the dialectical-critical method, based on critical social theory. Numerous instruments were used to collect data such as the application of an online questionnaire to the social workers of the municipal public schools of Limeira-SP; holding a focus group with the said social workers; documentary analysis of public tenders; municipal and state laws that create the position of social worker in basic education and Social Service legislation and other official subsidies published by CFESS in the relationship of Social Service with education and bibliographical research in dissertations and theses provided by CAPES, which were produced in the from 1988 to 2015 by the Graduate Programs in Social Work in the country. As theoretical contributions in the area of education, we used progressive authors from the approach of critical theory, such as Freire; Tonet, Mészaros, Sader, among others. For Social Service, we use Marxist authors, such as Iamamoto; Abreu; Raichellis; Prates; Martinelli, Guerra, among others. With regard to the theoretical foundation on Social Work in Education we use authors references in the subject, such as: Witiuk; Martins; Souza; Almeida; Amaro and Santos. Thus, our assumption is that the legislation in the area of Social Service, as well as the municipal laws and regulations contained in public bidding documents that deal with the insertion of Social Service in the municipal public school, do not beckon for the elucidation of what are the attributions developed in the professional practice of social workers in municipal basic education. As main results we show that the materiality on the insertion of social workers in municipal public schools occurs through the legislations, which present requirements for professional work in education. This insertion in the instruments of data collection is thought from general competences, attributions, or private assignments in front of the demands that justify the entry of Social Work in Education. And in this context, the attributions of the social worker in the municipal public school are shaped by their insertion in this reality, loaded with the founding elements of professional training such as critical thinking, the ethical-political project of the category, the code of professional ethics, the law of regulation of the profession, being conditioned the demands that are attributed to the Social Work in its professional exercise in the school. Thus, the professional work of the social worker in the public school is permeated by the tensions present in the capitalist system and the logic of education in the neoliberal context, which implies to say that the social workers are clear as to their assignments to the professional work developed in basic education, which differ in this scenario with a professional practice focused on education beyond capital.